Pengaruh Media Visual Pada Materi Menyusun Huruf Nama Benda Terhadap Motivasi Belajar Siswa - Windi Pujasari; Ani Sri Mulyani; Hani, Umi (MURABBI, 2023)
Currently grade 1 students sometimes feel lazy in understanding learning material and writing. According to the researchers, this is because students at this age have not been confronted directly with things that are real or contextual. Moreover, seeing the characteristics of grade 1 elementary school children is concrete operational, that is, they must be confronted with something real. The purpose of this study was to determine the effect of visual media on students' motivation in the material "Knowing the names of objects" at SD Plus Babussalam in the 2022/2023 school year. The research method used is quantitative description by conducting classroom action research. Data collection techniques were carried out by observation, questionnaires and documentation. The results of this study indicate that the effect of visual media on the material of knowing the names of objects for grade 1 SD Plus Babussalam, 90% of students agree that learning using visual media greatly influences student learning motivation.